Election night Bruce Bronzan Victory for District 3 Supervisor - Watkins, Howard K. (1976)
Bruce Bronzan and supporters at campaign headquarters,Peggy Bronzan in far back; center Bill Carlson, Doug Jones, Chloe French, Bruce Bronzan, ?, Nyla Hallum